Fully developed forced convection H2O-CuO nanofluid flow through concentric pipes annular sector duct by using KKL model. (May 2023) - Ahmed, Farhan
Fully developed hydro-thermal H 2 O - CuO nanofluid flow through concentric pipes annular sector duct is carried out. Koo–Kleinstreuer–Li ( KKL ) model correlations are taken into account to discuss the forced convection flow under the effect of Brownian motion. For discretizing and numerical simulation of governing mathematical problem, finite volume based method, ( FVBM ) and well known technique "semi implicit procedure for pressure linked equations, ( SIMPLE ) revised" are utilized, whereas constant axial wall heat flux with uniform peripheral wall temperature and, constant and uniform wall temperature known as H 1 and T thermally fully developed conditions respectively, are used to discuss the heat transfer rate for different contribution of "Copper Oxide ( CuO )" nanoparticles, n, in base fluid "pure water". By adding the contribution of nanoparticles, the enhancement in fanning friction factor, f Re, and average Nusselt number, Nu, has been estimated upto 7.72% and 7.54% respectively, in H 1 thermal case, whereas 7.71% and 7.16% respectively, in T thermal case.